P14.12 Gyriform infiltration as imaging biomarker for adult diffuse astrocytic glioma, IDH wildtype, with molecular features of glioblastoma. (9th September 2021) - Mesny, E; Barritault, M; Izquierdo, C; Poncet, D; d'Hombres, A; Guyotat, J; Jouanneau, E; Ameli, R; Honnorat, J; Meyronet, D; Ducray, F
Abstract: BACKGROUND: Diffuse astrocytic gliomas, IDH wildtype, with molecular features of glioblastoma (molecular glioblastomas) are associated with a poor prognosis. We previously found that these tumors frequently display gyriform infiltration, defined as areas of elective cortical hypersignal on MRI FLAIR sequence. The objective of the present study was to assess the diagnostic value of gyriform infiltration as an imaging marker for these tumors. MATERIAL AND METHODS: MRI scans from 430 patients with newly diagnosed glioma (molecular glioblastoma n = 31, IDH wildtype glioblastoma n = 298, IDH-mutant astrocytoma n = 50, IDH-mutant and 1p19q codeleted oligodendroglioma n= 51) were evaluated for the presence of a gyriform infiltration by 2 independent reviewers. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated to assess the performance of the presence of a gyriform infiltration for identifying molecular glioblastoma. RESULTS: A gyriform infiltration was observed in 16/31 (52%) patients with a molecular glioblastoma, 40/298 (13%) patients with an IDH-wildtype glioblastoma but in none of the patients with an IDH-mutant astrocytomas or an IDH-mutant and 1p19q codeleted oligodendroglioma. Among the 56 patients with a gyriform infiltration, 54 patients had an IDH wildtype pTERT mutant glioma and 2 an IDH wildtype pTERT wildtype glioma. Interrater agreement was good (κ= 0.68, P < 0.001). Specificity, sensitivity, PPV and NPV of the presence of a gyriform infiltration for the diagnosis of molecular glioblastoma were 90%, 29%, 52% and 96% and for the diagnosis of an IDHwt pTERT mutant glioma were 97%, 15%, 96% and 20%. The presence of a gyriform infiltration was associated with a worse prognosis in the entire cohort (13.6 months vs 29.3 months, P = .001). CONCLUSION: Gyriform infiltration is a specific imaging marker of molecular glioblastomas and IDH wildtype pTERT mutant diffuse gliomas.